(3GdchcH GdKGbH aj CNHGQ GdTYQGA hZjQge ef Phi GdefGbHs - (3GHf YHO GdQMef , YHO GdbGOQ Hf YHO GdQMef GdCfOdSj,J (B1180 (3g` s
(3ChdgG (B:s
(3fMeOc jGef CfWb dSGf GdGfSGf HLhGeY Gdcde hHOGFY GdMce s
(3Cdag SfI (B1176s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B39s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B220 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdJjehQjI (B((3JGQjN (B335) s
Keywords: (3GdJGQjNs